ASSEMBLING OF EROSION TEST APPARATUS AND THE INFLUENCE OF IMPACT ANGLE ON SLURRY EROSION RATE - SADAN, MAHDI KHIDER (Journal of Duhok University, 2023)
A Jet erosion tester is designed and assembling then used to study the relative erosion behavior of high density polyethylene (HDPE) with specific concentration of silica sand as an abrasive material, during varying impingement angles and specific size of abrasive particles. The water flow was turbulent. The test samples were mounted on sample holder and which has a provision to move in different angular positions to find out the erosion wear for different angles. The experiments were carried out using silica sand as erodent with a particle size range of (500-599) μm. Were used varying impact angles (90°, 60°, 45° and 30°) and solid abrasives of (2% wt.) concentrations have been used as fixed parameter for 20 hours. The concentration of slurries can vary from (2% to 50%) depending upon the type of slurry. Three samples were taken for each angle and the average was taken to obtain accurate results and was evaluated. The results which have been obtained shows that the erosion rate of (HDPE) was maximum at impact angle (45°) and minimum at (30°)